Urgent need for a South Asian hematopoietic stem cell donor registry - Srinivasan Periathiruvadi (Global Journal of Transfusion Medicine, 2018)
For over four decades, Haematopoietic Stem Cell Transplantation remains the only form of curative treatment of patients with blood cancers, Thalassemia and certain congenital immune deficiencies. Poor representation of Asian population in the global donor database and absence of a regional registry for South Asian population is responsible for loss of lives. Hence there is an urgent need for member countries in the SAARC region to work together to enable quick and affordable access to matching stem cells for patients in this region.